Implementation of the Contextual Teaching and Learning Model to Improve Students' Conceptual Understanding in Science Learning at MIN 5 Lhokseumawe - Susanti; Putri Salma (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to improve students’ conceptual understanding in science learning through the implementation of the Contextual Teaching and Learning (CTL) model at MIN 5 Lhokseumawe. The research employed Classroom Action Research (CAR) consisting of two cycles, with each cycle involving four stages: planning, action, observation, and reflection. The participants were 28 fifth-grade students at MIN 5 Lhokseumawe during the 2024/2025 academic year. Data were collected through conceptual understanding tests, observation sheets of teacher and student activities, and field notes. The indicators of conceptual understanding included students’ ability to explain scientific concepts, classify objects based on characteristics, provide examples of concepts, and apply concepts in daily life contexts. The findings revealed a significant improvement in students’ conceptual understanding after the application of CTL. In the pre-cycle phase, only 10 out of 28 students (35.71%) achieved the minimum mastery criterion (MMC = 75), with an average score of 68.21. After the implementation of CTL in Cycle I, the number of students who achieved mastery increased to 18 students (64.29%) with an average score of 75.46. Furthermore, Cycle II showed stronger improvement, with 25 students (89.29%) achieving mastery and the average score rising to 84.32. Observation results also indicated improvements in learning engagement, where student activity increased from 70.15% in Cycle I to 87.60% in Cycle II, while teacher performance improved from 76.40% to 90.25%. These results confirm that the CTL model effectively enhances students’ conceptual understanding in science learning by connecting scientific content with real-life situations, promoting active participation, and encouraging meaningful learning experiences. Therefore, CTL is recommended as an effective instructional approach for improving conceptual understanding in science education at the elementary Islamic school level.